Wound healing in surgery for trauma (WHIST): statistical analysis plan for a randomised controlled trial comparing standard wound management with negative pressure wound therapy - Knight, R; Spoors, L; Costa, M; Dutton, S (Biomed Central, 2019)
Background In the context of major trauma, the rate of wound infection in surgical incisions created during fracture fixation amongst patients with closed high-energy injuries is high. One of the factors which may reduce the risk of surgical site infection is the type of dressing applied over the closed incision. The WHIST trial evaluates the effects of negative-pressure wound therapy (NPWT) compared with standard dressings. Methods/Design The WHIST trial is a multicentre, parallel group, randomised controlled trial. The primary outcome is the rate of deep surgical site infection at 30 days after major trauma. Secondary outcomes are measured at 3 and 6 months post-randomisation and include the Disability Rating Index, the EuroQoL EQ-5D-5 L, the Doleur Neuropathique Questionnaire, a patient-reported scar assessment, and record of complications. The analysis approaches for the primary and secondary outcomes are described here, as are the descriptive statistics which will be reported. The full WHIST protocol has already been published. Discussion This paper provides details of the planned statistical analyses for this trial and will reduce the risks of outcome reporting bias and data driven results. Trial registration International Standard Randomised Controlled Trials database, ISRCTN12702354. Registered on 9 December 2015.